Legal Pluralism in the Context of the Distribution of Women’s Inheritance: Constellation of State, Islamic and Customary Laws - Sinaga, Istiqomah; Nurhayati; Affendi Mohmad Razali, Hazrul (Mazahibuna: Jurnal Perbandingan Mazhab, 2022)
This paper is a legal pluralism research on the partition of women’s inheritance. It investigates the reality that not all existing and applicable legal laws are being followed. Furthermore, the distribution of women’s inheritance is regulated in the Compilation of Islamic Law regarding the share of an heir. There is also a judicial institution that resolves disputes with material law and is accessible to the community. However, it is not always used as a downstream dispute resolution that involves inheritance. The emergence of customary law amongst other diverse sources cannot be ignored as having its place within society, which is frequently used to address normatively controlled legal issues. The results of this study showed the settlement of inheritance is not always handled by trial or litigation, particularly for indigenous peoples in Padangsidimpuan City. Hence, to minimize conflict, it is better to decide inheritance issues by consensus amongst families, with regulations that are ambiguous but geared toward the common interest. This paper is expected to be a study among legal practitioners and academics, even though law has restricted the inheritance share of each heir, and society strives to avoid litigation and settle disputes amicably. Therefore, his study can be pursued by examining whether other indigenous groups handle inheritance disputes in the same manner.